?INDUCED HISTOLOGICAL CHANGES IN PISTACIA VERA L. COTYLEDONARY TISSUE - JABEEN, SHAISTA; ZAIDI, NASREEN; ZAFAR, FERHA; IQBAL, MUHAMMAD ZAFAR; SHAH, F.H. (Biological Sciences - PJSIR, 1995)
Pistacia vera cotyledonary explants cultured on MS-Murashige and Skoog medium: WP-Woody plant medium: EK-Eriksson medium and Sl l-Schcnk and Hildebrandt medium formed calli of different quantity and quality. Per- centage gain in callus mass was maximum on WI’ medium. relatively double in amount as compared to the rest of the mediums, MS, EK or SH. Calli were white to dark brown in colour and nodular/friable in texture. Active growth of the calli ended in browning of the tissue which led to slow growing new white soft calli. Browning tendency of the cultures was same in case of slow or rapidly growing ones. Effect of replacing macro and micro nutrients of each on browning and callus mass gain was also studied. Interchange of MS and WI’ macro and micronutricnts produced . more calli as compared to those of SH and EK. Histological examination of the calli revealed various morphogenetic changes. Wound callus and xylogenesis were observed on combination of MS micro and WP macronutrients. While caulogenesis was observed on MS macro and WI’ micronutrient combination.